Intercomparison of 3D pore-scale flow and solute transport simulation methods. (September 2016) - Yang, Xiaofan; Mehmani, Yashar; Perkins, William A.; Pasquali, Andrea; Schönherr, Martin; Kim, Kyungjoo; Perego, Mauro; Parks, Michael L.; Trask, Nathaniel; Balhoff, Matthew T.; Richmond, Marshall C.; Geier, Martin; et al.
Highlights: Reports a large 3D benchmark study of pore-scale modeling methods. Codes and methods varied widely in complexity and computational demand. Both macroscopic and local measures of flow and solute transport were evaluated. Comparisons were generally favorable among the various methods. Differences observed support method selection depending on problem context. Abstract: Multiple numerical approaches have been developed to simulate porous media fluid flow and solute transport at the pore scale. These include 1) methods that explicitly model the three-dimensional geometry of pore spaces and 2) methods that conceptualize the pore space as a topologically consistent set of stylized pore bodies and pore throats. In previous work we validated a model of the first type, using computational fluid dynamics (CFD) codes employing a standard finite volume method (FVM), against magnetic resonance velocimetry (MRV) measurements of pore-scale velocities. Here we expand that validation to include additional models of the first type based on the lattice Boltzmann method (LBM) and smoothed particle hydrodynamics (SPH), as well as a model of the second type, a pore-network model (PNM). The PNM approach used in the current study was recently improved and demonstrated to accurately simulate solute transport in a two-dimensional experiment. While the PNM approach is computationally much less demanding than direct numerical simulation methods, the effect of conceptualizing complex three-dimensional pore geometries on solute transport in the manner of PNMs has not been fully determined. We apply all four approaches (FVM-based CFD, LBM, SPH and PNM) to simulate pore-scale velocity distributions and (for capable codes) nonreactive solute transport, and intercompare the model results. Comparisons are drawn both in terms of macroscopic variables ( e.g., permeability, solute breakthrough curves) and microscopic variables ( e.g., local velocities and concentrations). Generally good agreement was achieved among the various approaches, but some differences were observed depending on the model context. The intercomparison work was challenging because of variable capabilities of the codes, and inspired some code enhancements to allow consistent comparison of flow and transport simulations across the full suite of methods. This study provides support for confidence in a variety of pore-scale modeling methods and motivates further development and application of pore-scale simulation methods.